Menggugah Imajinasi dan Minat Baca: Program Literasi di Kecamatan Kotaanyar, Kabupaten Probolinggo - Susetya, Hemas Haryas Harja; Fatmawati, Malinda (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
This article documents a literacy program carried out in the Kotaanyar Subdistrict, Probolinggo Regency, with the primary goal of stimulating imagination and reading interest among adolescents. The program explores various creative and interactive approaches to enhance literacy within the community. This article provides insights into the stages of program implementation, including planning, execution, and its impact on participants. The literacy program encompasses not only book reading activities but also book discussions, the establishment of reading spaces, and various engaging literacy activities. One of the program's main focuses is intensive mentoring to stimulate adolescents' reading interest and foster their creativity. The article also emphasizes the importance of collaboration with various stakeholders, including participants' families, local schools, and local government, in efforts to create a sustainable literacy culture. The outcomes of this literacy program include increased reading interest among adolescents, the development of creativity, changes in reading culture, and improvements in the quality of education. This article illustrates how a literacy program can be an effective instrument in enhancing literacy and awakening creative potential within the local community. It is hoped that the experiences and lessons learned from this program can inspire and guide similar efforts in other locations.